Pendekatan Community Language Learning dalam Pembelajaran Bahasa Arab: Kajian Konseptual dan Implementatif - Tiana Nur Azizah Suparman; Channah Qotrunnada; Ahmad Khalil; Nanang Kosim (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study explores the Community Language Learning (CLL) method in Arabic language instruction using a literature review approach. CLL emphasizes affective, social, and collaborative learning, with the teacher acting as a counselor and facilitator. The study discusses the historical and theoretical foundations of CLL, its core principles, implementation stages, application examples in Indonesia, and an analysis of its strengths and weaknesses. Findings indicate that CLL effectively enhances students’ speaking skills, confidence, and active participation. However, challenges such as limited instructional time, teacher readiness, and student proficiency gaps remain. This study recommends integrating CLL with educational technologies and 21st-century learning strategies to optimize its application in Arabic language education institutions.